Лирика: поэзия : (16+) / Эдуард Асадов - Асадов Эдуард Аркадьевич (Русская классика, 2015)
Экземпляры: ф.11 (20151112) / Инвентарный номер: 059628 / Цена: 204.00 / Авт.знак: А 90 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6